Technology-policy gap and impact on application of animal biotechnology in sub-Saharan African countries - Oluoch-Kosura,Willis; Odhiambo, M.O. (TSAP and ILRI, 2006)
The livestock sector continues to play a major role in the economies of many sub-Saharan African countries. Predictions indicate that demand for livestock products will increase in the coming decades due to increasing human population and urbanisation. This calls for enhanced livestock production and productivity, which will require and will clearly involve increased intensification while also ensuring that the systems are resource efficient. Livestock diseases and the need for sustainable natural resource management are among the key challenges that need to be addressed. Although livestock research has over the years been directed at addressing these issues, little progress has been made in sub-Saharan Africa. Conversely, the application of biotechnology, for example in animal health, has significantly benefited developed countries more than African countries. This paper addresses the apparent gap between research and technology generation and adoption of the technologies on farms, especially by smallholders in sub-Saharan Africa. It is argued that science and technology policy if it exists, does not address the constraints faced by the farmers in a way that would facilitate adoption. The constraints include inadequate infrastructure, markets, capacity building, extension, credits, tenure system and institutions among other factors. Governments ought to address these issues at policy level as a way of accelerating widespread application of livestock biotechnologies particularly for increased productivity and profitability in the sub-sector. Moreover, concerted efforts from the national and international community in addressing issues of intellectual property rights, biosafety regulations and rules, fair trade, as well as effective and open communication between researchers, policymakers and technology users would be required.